PRODUCTION AND REPRODUCTION PERFORMANCE OF NELLORE SHEEP IN (NATIVE BREEDING) CHITTOOR DISTRICT OF ANDHRA PRADESH - B. PUNYA KUMARI, M. RANI, B. EKAMBARAM and (The Journal of Research, PJTSAU, 2019)
The analysis of field data on 1350 Nellore Jodipi sheep maintained by farmers under field conditions of Andhra Pradesh revealed that the effect of division and sex had significant (P